THEORETICAL AND TERMINOLOGICAL ASPECTS IN CONCEPTUALIZING METHODICS OF EDUCATIONAL WORK AS A PEDAGOGICAL DISCIPLINE (Annual of the Faculty of Philosophy in Skopje, 2023)
The importance of pedagogy as a science is in exploration and improvement of education as an integral part of the social reality. Theory of education, General pedagogy and Methodics of educational work are the scientific disciplines that are most directly related to examining the educational work, and represent its theoretical and methodological basis in the process of its realization. Educational work provides the essence of the overall education process, since it refers and unites the knowledge, skills, attitudes, beliefs and values of the individual, and its results are seen in developing student’s unique personality. In this paper the focus is on the Methodics of educational work, as a pedagogical discipline which is most closely related to the process of realization of educational work. The aim is through analysis of the basic theoretical and terminological aspects to emphasize its role in the overall education process. Taking into consideration the complexity of educational work and difficulties related to the process of assessment of the outcomes, application of the taxonomy of the affective domain is suggested as a possible approach. Also, the importance of some topics that are particularly relevant in pedagogy is emphasized, but which, due to terminological inconsistencies, are not sufficiently recognized as part of the Methodics of educational work.
Keywords: education; educational work; education process; assessment